Comparative Analysis on Application of 240 V Direct Current Power Supply System and Modular UPS in Data Center - Yan Hu; Jieliang Lou (Dianxin kexue)
The application scale of 240 V direct current power supply system and modular UPS is expanding continuously. The advantage and characteristics of the two power supply systems were studied, the user acceptance, the availability of power supply system, and the total cost of the whole life cycle were comparatively analyzed. Some specific concerns regarding the application in data center were raised, such as load adaptability testing, redundancy allocation principle, and so on.